Topologie: 1. bis 7. Sept. 1963 - Dold, Albrecht; Schubert, Horst; Puppe, Dieter (Tagungsbericht, 1963)
M. André, Genf; F. W. Bauer, Frankfurt a. M.; E. Brieskorn, Bonn; H. B. Brinkmann, Saarbrücken; R. Brown, Liverpool; H. Cartan, Paris; H. Debrunner, Bern; P. Dedecker, Liège; M. Deruaz, Zürich; T. tom Dieck, Saarbrücken; D. Epstein, Cambridge; A. Frei, Zürich; M. Fuchs, Saarbrücken; G. Grimeisen, Stuttgart; G. Hirsch, Brüssel; H. Holmann, Münster; L. Horowitz, Leiden; H. Ibisch, Tübingen; K. Jänich, Bonn; J. Jaworowski, Warschau; F. Kamber, Zürich; K. Lamotke, Bonn; S. Mardesić, Zagreb; C. Morlet, Reims; M. Moss, Hull; J. R. Porteous, Liverpool; W. Shih, Paris; E. Stamm, Zürich; B. Steer, Oxford; W. Thöni, Zürich; Ph. Tondeur, Zürich; I. Valderrama, Brüssel; C. T. C. Wall, Cambridge; A. Van de Ven, Leiden; E. C. Zeeman, Cambridge